Implementation of Q.S. An-Nahl Verse 125 to Improve Islamic Understanding in Class II A Women's Penitentiary in Bandung - Mikdar, Wendi Saepul; Saodah, Odah (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2024)
Da'wah is a demand for every Muslim, because one of the main tasks of the Messenger of Allah who was sent was to preach among people with various characters, so that when the Messenger of Allah invited them to the right path, they had to use appropriate methods so that the invitation was accepted. freely without coercion. The Class II A Bandung Women's Penitentiary is a part that is affected by Islamic preaching, because it contains inmates who are involved in various cases. The application of the interpretation of An-Nahl verse 125 in women's correctional institutions aims to increase the Islamic understanding of prisoners so that even though they are serving time, religious activities can still be carried out. Keywords: Tafsir, Education, Islamic.   Abstrak Dakwah adalah tuntutan bagi setiap muslim, karena salah satu tugas utama Rasulullah saw diutus adalah untuk berdakwah di tengah-tengah masyarakat yang bermacam- macam karakter, sehingga ketika Rasulullah saw mengajak mereka kepada jalan yang benar harus dengan metode-metode yang sesuai agar ajakan itu diterima dengan lapang dada tanpa paksaan. Lembaga Pemasyarakatan Perempuan kelas II A Bandung merupakan bagian yang terkena dakwah Islam, karena didalamnya terdapat para narapidana yang terjerat bermacam- macam kasus. Penerapan tafsir An-Nahl ayat 125 di lingkungan lembaga pemasyarakatan perempuan bertujuan untuk meningkatkan pemahaman keislaman para narapidana sehingga meskipun dalam keadaan sedang menjalani hukuman, kegiatan keagamaan tetap terlaksanakan. Kata kunci: Tafsir, Pendidikan, Keislaman